EVALUASI PEDIATRIC TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN LAYANAN KESEHATAN ANAK DI RSUD JARAGA SASAMEH KALIMANTAN TENGAH - I Made Samitha Wijaya; Rian Andriani; Rizki Adriansyah Rubini (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Total Quality Management (TQM) is a comprehensive approach in quality management that involves all members of the organization in efforts to improve quality. Implementation of TQM in hospitals can be an effective solution to improve quality Management, especially in Pediatric patient services at Jaraga Sasameh Regional Hospital. It is necessary to strengthen quality Management in Pediatric services by increasing staff training and education on Pediatric care, providing special facilities and equipment for Pediatric patients, developing special protocols and guidelines for Pediatric patient care, implementing a child-friendly approach in services, increasing supervision, reporting, and analysis of adverse events involving patients. A summary of these activities and a series of program systems formed in Pediatric Total Quality Management in efforts to improve quality Management, improve services and satisfaction of Pediatric patients at Jaraga Sasameh Regional General Hospital. The purpose of this study was to evaluate Pediatric Total Quality Management in improving Pediatric health services at Jaraga Sasameh Regional Hospital, Central Kalimantan. The design of this study was descriptive observational in the form of interviews about Pediatric Total Quality Management in health services. Interviews were conducted with 8 health workers who worked in the children's and infant rooms of Jaraga Sasameh Regional Hospital. The conclusion of this study is that the implementation of Pediatric Total Quality Management in terms of quality, quantity, timeliness, effectiveness, and work commitment has been running well, but there are some things that still need to be improved such as the availability of drugs, medical devices and medical calm training to support better patient services.